Hattori-Zyste – eine seltene Läsion im posterioren Mediastinum - Elsner, Felix; Khamitov, Koblandy; Hinsen, Maximilian; Sirbu, Horia; Hartmann, Arndt (Die Pathologie, 2024)
CRIS-Team Scopus Importer:2024-05-24

TAT-CRE inhalation enables tumor induction corresponding to adenoviral Cre-recombinase in a lung cancer mouse model - Gewalt, Tabea; Dmitrieva, Anna M.; Elsner, Felix; Zhao, Xinlei; Sieber, Daniel Dimitri; Kocak, Ilayda Gülsen; Yang, Qian; Orschel, Claudia Viktoria; Eckert, Naja Maria; Goebel, Bianca; Nill, Marieke; Peter, Fiona; et al. (Communications Biology, 2025)
Cre-recombinase inducible model systems are extensively used in cancer research to manipulate gene expression in specific tissues and induce autochthonous tumor growth. These systems often involve the cross-breeding of genetically engineered organisms containing loxP-flanked alleles with those expressing Cre-recombinase. This approach, while effective, has the challenge of requiring high numbers of animals due to breeding requirements. Other frequently used tumor induction methods in cancer research involve the direct application of viral Cre-recombinase vectors. This approach presents the challenge of the accessibility of facilities that meet the necessary safety level. In this context, we perform a comprehensive comparison between TAT-CRE (biosafety level S1) and adenoviral Cre-recombinase induced (biosafety level S2) lung adenocarcinomas driven by KrasG12D expression and Trp53 depletion. We use in vivo lung tumor monitoring via computed tomography, single-cell RNA sequencing, immunohistochemistry and flow cytometry to elucidate similarities and differences between TAT-CRE and adenoviral Cre-recombinase induced lung adenocarcinomas. TAT-CRE induced lung tumors present differences in micro-vessels and macrophages but with corresponding tumor onset and growth characteristics compared to adenoviral-Cre recombinase induced lung tumors. Taken together, TAT-CRE is a valuable genetic engineering safety level S1 alternative for cancer induction and may be implemented in other cancer models than lung cancer.
CRIS-Team Scopus Importer:2025-05-23

Tumor-in-tumor metastasis: a rare phenomenon Tumor-in-Tumor-Metastase: Ein seltenes Phänomen - Elsner, Felix; Keller, Katharina; Fuchs, Florian; Uder, Michael; Hartmann, Arndt (Die Pathologie, 2024)
CRIS-Team Scopus Importer:2025-02-04